No Man's Land : Globalization, Territory, and Clandestine Groups in Southeast Asia - Hastings, Justin V. (Justin VanOverloop) (Book collections on Project MUSE., 2010)
Based on often difficult fieldwork in Southeast Asia, Hastings traces the logistics networks, command and control structures, and training programs of three distinct clandestine organizations: the terrorist group Jemaah Islamiyah, the insurgent Free Aceh Movement, and organized criminals in the form of smugglers and maritime pirates Hastings also compares the experiences of these groups to others outside Southeast Asia, including al-Qaeda, the Tamil Tigers, and the Somali pirates. --Book Jacket.